LpxR and PagL expression in live attenuated auxotrophic Pseudomonas aeruginosa vaccines modulates lipid A reactogenicity in vitro while preserving immunogenicity - Moscoso, Miriam; Fuentes-Valverde, Víctor; García, Patricia; Vallejo, Juan A.; Pérez-Ortega, Jesús; Santamarina-Fernández, Rebeca; Candela, Ana; Oviaño, Marina; Arenas, Jesús; Bou, Germán (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionPseudomonas aeruginosa is a Gram-negative opportunistic pathogen responsible for severe respiratory tract infections. We previously developed a live attenuated auxotrophic vaccine candidate, PAO1 ΔmurI, which conferred protection in murine infection models but exhibited significant reactogenicity when administered intranasally. To reduce the toxicity of PAO1 ΔmurI without compromising its protective efficacy, we engineered strains with a modified lipid A structure, as lipid A is one of the main toxic components of whole-cell vaccines.MethodsTwo lipid A-modifying enzymes, LpxR and PagL were overproduced in PAO1 ΔmurI derivatives. The resulting lipopolysaccharide (LPS) was analyzed by MALDI-TOF mass spectrometry. In vitro assays with HEK293-Blue reporter cells expressing murine and human Toll-like receptor 4 (TLR4) were used to assess LPS-associated toxicity, while in vivo reactogenicity and protective efficacy were evaluated in a murine acute pneumonia model.ResultsLPS extracted from the wild-type strain showed heterogeneous lipid A structures with varying degrees of acylation, and a predominant penta-acylated species. Expression of LpxR led to enrichment in tetra-acylated species, while PagL expression reduced the heterogeneity observed in the wild type. Both mutant strains showed decreased TLR4 activation in vitro as compared to the wild type. In mice, lipid A-modified derivatives retained protective efficacy; however, no reduction in reactogenicity was observed.DiscussionLipid A modifications mediated by LpxR and PagL attenuated TLR4 signaling in vitro but were insufficient to reduce in vivo reactogenicity. Additional modifications or targeting of other toxic components may be required. This strategy may serve as an initial basis for optimizing live attenuated P. aeruginosa vaccines, although additional approaches will likely be necessary to achieve substantial improvements.